Residents resilience towards insecurity: an analysis of socioeconomic and demographic profile of respondents in Maiduguri, Borno State, Nigeria - Butu, Hauwa Mai; Hashim, Ahmad Hariza; Ahmad, Nobaya (International Organization Of Scientific Research, 2017)
The study describes the socioeconomic and demographic profile of Maiduguri residents on resilience towards insecurity, using convenient sampling technique, with a sample size of 383. The descriptive statistics was to describe the socioeconomic and demographic profile of the respondents. The results revealed that, the majority of residents are within the age bracket of 18-35, married, Muslims, and those who has tertiary education account for 603% of the majority. The result also indicates that most residents of the area are civil servant and business owners with few engaging in farming.Most of the residents lived in rented houses as compare to an owner occupier. The majority of the residents reside in the area for 1-10 years, while a large proportion falls with in low-income bracket of N10,000-N30,000. The socioeconomic and demographic profile of the residents will provide relevant information on the actual condition of the residents and what the affected residents need most in terms of assistance that would improve their condition and relief them of the hardship been posed on them by the insurgency predicament.